PENGARUH TEKNIK REFRAMING UNTUK MENGURANGI LEARNED HELPLESSNESS MELALUI BIMBINGAN KELOMPOK DI SMP NEGERI 29 PEKANBARU - Galuh Ratna Handari; Rosmawati Rosmawati; Roby Maiva Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine the differences in learn helplessness of students before and after the application of reframing techniques through group guidance and knowing the effect of reframing techniques to reduce the helplessness of students' learning through group guidance. This research was conducted at SMP Negeri 29 Pekanbaru on 7 subjects with purposive sampling technique. The design of this study was pre-experiment with the one group pre-test post-test model. The data collection instrument conducted is a scale of measurement of learned helplessness. The results showed that there were differences in learn helplessness of students before and after the reframing technique was given with a significance value of 0.018 <0.05. In addition, based on the Spearman rank test it is known that there is a significant influence between reframing techniques to reduce learned helplessness with a significance value of 0.033 <0.05. The effect of reframing technique to reduce learned helplessness is 62.8% while 37.2% is influenced by other factors that come from within and from the student's environment. From the results obtained, it is recommended that educational institutions should continue to carry out activities that are able to reduce students' learned helplessness in the teaching and learning process to encourage more positive cognitive, motivational and emotional improvement.Key Words: Reframing, Learned Helplessness Techniques, Group Guidance